Discourses on Learning in Education:Making Sense of a Landscape of Difference - Davis, Brent; Francis, Krista (Frontiers in Education, 2021)
There are hundreds, perhaps thousands of “theories of learning” at play in the field of education. Given scant agreements on the meaning of “learning” and the purpose of “theory,” such quantity is perhaps unsurprising. Arguably, however, this situation is indefensible and debilitating in an academic domain so focused on interpreting and influencing learning. We describe our own efforts to come to terms with this matter. Oriented by Conceptual Metaphor Theory and network theory, we are attempting to “map” contemporary treatments of learning – whether implicit or explicit, written or spoken, descriptive or prescriptive, formal or informal, scientific or folk. We report on our iterative process, evolving design, and emergent insights. We discuss the potential relevance of this and similar efforts for the future of educational research and practice.